INTERGRAREA TERMINOLOGIEI PORTULUI POPULAR ÎN LOCUȚIUNI ȘI EXPRESII INTEGRATION OF POPULAR PORT TERMINOLOGY IN SPEECHES AND EXPRESSIONS - Кібак, Діана Вікторівна (Universitatea de Stat „Bogdan Petriceicu Hasdeu” din Cahul, 2022)
From the description of the anthropo-geographic frame that is inherent to the items of traditional costume of Valea Siretului, up to the analysis of the specific terminology of the ethnographic region, our article represent a promoter of the ethnographic and ethnolinguistic culture that they have been creating as they define with dignity, by mens of their Romanian character, their historical, linguistic and cultural identity.
Keywords: Ethymology; Terminology of folk; Tradition